Gas chromatographic method validation for the analysis of major components in illicit heroin seized in Malaysia - Chan, K.W.; Tan, G.H.; Wong, R.C. (2012)
Apart from routine analysis of total morphine content required by the criminal justice system, quantification of other major components in illicit heroin has not been considered by the Malaysian enforcement laboratory. In order to quantify various other cutting agents in addition to alkaloids, a gas chromatographic (GC) method was developed to facilitate simultaneous quantification of eight target analytes commonly found in illicit heroin seized in Malaysia within a 12min run time. The validation results demonstrated high selectivity with the use of an HP Ultra 2 capillary column. Different solvents were studied and methanol:chloroform (1:9) proved best for sample dissolution. The method was repeatable and reproducible. The study ranges covering 50-150% of the preferred concentrations of the eight analytes obtained r(2)>0.9997. Limits of detection up to 6μg/mL were also obtained and the method achieved 99-102% recovery. The capability of the method in heroin profiling was verified using samples from ten case samples.